ФОРМИРОВАНИЕ КОМПЕТЕНТНОСТИ БУДУЩЕГО УЧИТЕЛЯ ФИЗИКИ НА ЛАБОРАТОРНЫХ ЗАНЯТИЯХ - Джораев, М.; Ахмедов, А. (SCIENCE and SOCIETY, 2018)
The article examines the issues of increasing the effectiveness of training used in educational process of the upgraded structure holding laboraty classes in formation of the competence of the teacher of Physics.
Keywords: laboratory activity; modernization; competence; application; future teachers in physics; the level; quality index; formation; experimental studies